IMPLEMENTASI MANAJEMEN KEPEMIMPINAN PAUD BERPUSAT PADA ANAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Annisa Rahman Santoso; Ayu Anjarwati; Niswatus Zahra; Sagita Faidatun Nikmah; Siswadi (STKIP Subang, 2026)
This study aims to analyze the implementation of child-centered leadership management in Early Childhood Education (PAUD) to improve learning quality. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of principals, teachers, and educational staff in an early childhood education institution. The results showed that the implementation of child-centered leadership management was carried out through planning learning programs based on children’s needs, organizing safe and attractive learning environments, implementing active play-based learning, and conducting continuous supervision and evaluation. The principal’s leadership strategy was also reflected through teacher coaching, strengthening teamwork, providing learning facilities, and building partnerships with parents. This implementation had a positive impact on improving learning quality, indicated by increased children’s active participation, teacher creativity, conducive learning atmosphere, and the development of children’s cognitive, social, emotional, and motor aspects. Supporting factors included principal competence, teacher professionalism, parental support, and adequate facilities, while inhibiting factors were limited budgets, lack of training, and low participation of some parents. Therefore, child-centered leadership management plays an important role in improving the quality of early childhood education services.